Small-signal AC model and closed loop control of interleaved three-phase boost converter - H.V.Gururaja Rao; Karuna Mudliyar; R.C. Mala (Institute of Advanced Engineering and Science, 2018)
Renewable energy sources are increasingly being used today and solar energy is the most readily and abundantly available energy source. Boost converters are an integral part of any solar energy system. In order to obtain maximum possible energy from the solar system multi-phase interleaved boost converters are used. This paper presents the small-signal ac modelling and closed loop control of three-phase interleaved boost converter. State–space modelling methodology has been adopted to have linearized equivalent model of the boost converter. The interleaved three-phase boost converter is averaged over its one switching period and perturbed with small ac variations and finally linearized around its quiescent point to have a small signal ac model. Type III compensator is employed to improve the frequency response and closed loop control of three-phase boost converter. The controller design procedure is discussed in detail. The effect of right-half plane zero in non-minimum phase system and the appropriate pole-zero placements to overcome the maximum phase lag in such system is discussed. The compensated closed loop system is tested for load variations to observe the transient response.